Mac OS X in a nutshell - McIntosh, Jason (O'Reilly, 2003)
Complete overview of Mac OS Jaguar (Mac OS X 10.2) including basic system and network administration features, hundreds of tips and tricks, with an overview of Mac OS X's Unix text editors and CVS.